Education And Training Model Strengthening Religious Moderation (Case Study At Medan Religious Training Center) - Siti Hawa Lubis; Purnomo Purnomo; Anan Nisoh; Muliatul Maghfiroh; Anri Naldi (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The challenges of religious moderation are the strengthening of exclusive religious views, attitudes, and behaviors, the high rate of religiously motivated violence, intolerance, the development of religious spirit that is not in harmony with the love of nation and state. The aim is to analyze how the education and training model strengthens religious moderation at the Medan Religious Training Center. This research method is qualitative with a case study approach. The results of the study found an educational model through four pillars of  learning, learning to know, learning to do, learning to  be, learning to live together. The education and training model for strengthening religious moderation in 2014-2019 is a substance model that finds a lot of debate and rejection, so that since 2019 until now the methodological model for combating religious moderation as a solution to solve the problems that occur. It was concluded that strengthening religious moderation in Indonesia is a challenge to the maturity of a multicultural nation. The education and training model must be updet to the times so that the challenges of religious moderation can be solved such as the methodology training model as a solution to solve problems in the aspect of religious moderation.